Proactive Service - เสมอใจ ฉัตยาพร (Journal of Humanities and Social Sciences, Rajapruk University, 2015)
Lots of business used the same tool or equipment in providing service but the response from customer was different. The quality of service was not only depended on the best tool or equipment, but also having good designed of service process was vital also. Furthermore, service provider who provided quality service was important part in building up satisfaction. When the loyalty level of non-experienced person in service problem had lower average of loyalty level than the experienced one, thus, the preparation of proactive service would increase more convenience to customer in all process or skip over some step of service. The result of survey in collecting marketing information from company’s service provider was founded that 87 percent of customer who required for proactive service and 73 percent of good experienced customer in proactive service had good perception toward the company as well. In addition, 62 percent of customer who received proactive service would obviously showed satisfaction on proactive service.